Sternal foramen as extracardiac findings in cardiac computed tomography - Spałek, Michał; Zychowska, Małgorzata; Wolak, Przemysław; Spałek, Jakub; Kuder, Tadeusz (Medical Studies/Studia Medyczne, 2016)
Introduction: According to the recommendations made by associations engaged in the diagnostics of cardiovascular diseases, a physician who interprets an imaging scan of this organ should consider in the report also changes in other structures covered by the examination. One of the structures observed in cardiac computed tomography (CCT) is the sternum. Aim of the research The authors of the presented article wish to pay attention to the developmental defect of this bone – the sternal foramen, which may sometimes be of importance in some medical and paramedical procedures. Knowledge concerning the presence of such a foramen in the patient subjected to the procedure of bone marrow trepanobiopsy or acupuncture may protect against dangerous complications resulting from the puncture of the heart structures or the large vessels of the mediastinum. Material and methods: Into the study group were qualified 134 patients (78 females and 56 males), aged from 29–84 years, in whom CCT was performed. Results: Sternal foramen was found in eight males and one female, the majority in the lower part of the body of the sternum. The results obtained did not differ from reports available in literature. Conclusions: Sternal foramen is a frequently observed developmental defect, which should always be included in the description of the CCT scan and other imaging tests covering the sternum. Preliminary results of the study suggest a significant correlation between the frequency of its occurrence according to gender; however, the confirmation or exclusion of such a relationship requires further analysis on a larger group of patients.